Biological and spatial structure of an early classic period cemetery at Charco Redondo, Oaxaca. Issue 2 (3rd September 2013) - Paul, Kathleen S.; Stojanowski, Christopher M.; Butler, Michelle M.
ABSTRACT This article presents an analysis of biological and spatial patterning of an Early Classic (A.D. 250–500) Chatino cemetery at the archaeological site of Charco Redondo, located in the lower Río Verde Valley, Oaxaca, Mexico. The Early Classic was a time of political instability positioned between two phases of state‐level centralization within the coastal valley. The communal cemetery at Charco Redondo adds significantly to the inventory of excavated graves from this time period and provides novel data on mortuary practices during a critical phase in the development of state level polities in the region. Cluster analysis of mortuary data is combined with intracemetery biodistance approaches to reconstruct how the Charco Redondo cemetery was organized with respect to biological relationships. Cluster analysis of mortuary data identified three groupings of burials. Multidimensional scaling of Euclidean distances and Gower coefficients based on 45 odontometric and 13 dental morphological variables suggests a strong relationship between grave characteristics and locations and phenotypic variation. In other words, the cemetery at Charco Redondo appears biologically kin‐structured. The communal nature of the cemetery conflicts with the assumed "household" burial model for this time period. We propose the observed combination of features represents a transitional practice in which aspects of community, kin, and individual identity were signaled simultaneously within the funerary environment during a time of political transition in the Valley. This article highlights the utility of intracemetery biodistance analyses for examining dimensions of kinship, "house, " and community throughout Mesoamerica where overarching models often mask regional variability. Am J Phys Anthropol 152:217–229, 2013. © 2013 Wiley Periodicals, Inc.